Exit-Site Care Adherence in Peritoneal Dialysis: Real-World Practice and Outcomes - Jadon Ryan Yang; Jason Ton; Maria Daraoay; Lukas Kairaitis; John Wing Li; Kamal Sud; Katrina Chau (Australasian Journal of Clinical Nephrology, 2026)
Introduction Peritoneal dialysis catheter-related infections represent a major source of morbidity, yet the optimal components of exit-site care and the role of patient adherence remain uncertain. This study evaluated real-world exit-site care practices, adherence, and associations with infection outcomes in a multicultural Australian peritoneal dialysis cohort. Methods A cross-sectional observational study was conducted within a metropolitan renal service. Adult patients attending routine follow-up completed a structured interviewer-administered survey capturing recalled training instructions, current practices, and reasons for non-adherence. Infection outcomes were obtained from registry and electronic medical record data, and adherence was assessed against both recalled instructions and local protocol. Results A total of 103 participants were included. Non-adherence to recalled training instructions was observed in 50% of participants, while 47% did not meet local protocol requirements. Exit-site care practices varied substantially, particularly regarding antiseptic choice and cleansing frequency. Peritonitis and catheter-related infection rates were low (0.26 and 0.11 episodes per patient-year, respectively) and within guideline targets. No significant associations were identified between adherence measures or specific care practices and infection outcomes. Adverse reactions, most commonly related to antibacterial honey, were the leading reason for deviation from recalled instructions. Conclusion Substantial heterogeneity in exit-site care practices was observed without evidence of worse infection outcomes. Within this local context, strict adherence to intensive exit-site care regimens may not be necessary to maintain acceptable infection rates when minimum hygiene standards are preserved. Simplified approaches prioritising tolerability may improve sustainability and patient acceptability without compromising safety.